PEMBERDAYAAN WARGA MELALUI USAHA PEMBUATAN BESEK DI GUMAWANG GUNUNG KIDUL - Astuti, Reni Dwi; Budiyanto, Tri; Faishal, Muhammad (Universitas Ahmad Dahlan, Yogyakarta, 2018)
Gumawang is an area with lots of bamboo, so many bamboo craftsmen in the area. However, production capacity is still low and cannot meet market demand. This is due to the small number of craftsmen (approximately 10 people) and the low number of workers who carry out the bamboo process. In addition, product quality is low, because it is easily damaged (moldy) caused by the water content in the product is too high, especially in the rainy season. Another problem encountered is a non-ergonomic work system and no financial accounting. To solve the problem, a solution was offered in the form of training for Gumawang residents to increase the number of craftsmen, use of product drying technology to reduce water content so that products last longer, counseling on ergonomics, and training on financial management. Another benefit of the service program is increasing the income of craftsmen and residents in general.